Performance of Automotive SLI Battery under Constant Current Constant Voltage Charge Algorithm in Solar PV Application (Journal of Science and Technology, 2016)
The high initial cost of deep-cycle PV battery and its high replacement cost constitute an important barrier to the deployment of solar PV technology, particularly in poor rural settings. Battery lifetime depends on effective charge control and load management. In this project, a cost-effective 12V battery charge controller was developed to implement constant current constant voltage charge algorithm in small-sized stand-alone solar PV systems. The algorithm was tested on automotive SLI battery instead of deep-cycle PV battery to further reduce overall system cost. The battery state of charge (indicated by specific gravity), which is an indicator of algorithm performance, was monitoredover 200 daily charge/discharge cycles. The value of the specific gravity ranged from 1.250 to 1.260, demonstrating the effectiveness of the control algorithm.